Nucleic acid assembled semiconducting materials: Rational design, structure–property modulation, and performance evaluations - Dan Bai; Wenxuan Zhao; Huhu Feng; Hiroshi Sugiyama (APL Materials, 2023)
Nucleic acids are widely recognized as the most evolved information processing soft material, possessing intrinsic efficiency in transferring and harvesting photon, electron, and energy. Recent developments in semiconductor synthetic biology and nanophotonics have spurred significant research efforts toward modifying and modulating nucleic acid assemblies. Given the rapid advances in using carbon-based hybrid materials for renewable energy, information technology–biotechnology fusion, and medicine, this review highlights recent research on nucleic acid-assembled hybrid materials, their design rationale, and performance modulation according to various application scenarios. Bridging the gap between molecular functionalization and material engineering, this review aims to provide a systematic analysis for researchers, engineers, and end-users to make informed decisions promptly.